Metaphorical Switching in a Formal Interview Conducted in Indonesian - Frina Diniarta Nur (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2019)
Metaphorical switching is a common phenomenon in bilingualism. It is the speakers’ tendency to switch codes within a single conversation. This research intends to investigate the occurrence of metaphorical switching in a formal interview conducted in Indonesian language. This research uses qualitative method and the data are taken from the formal interview on Elshinta radio. Five questions are intended to answer. The first is whether English is the only code used when the interviewer and the interviewee metaphorically switch code during the interview. The research shows that the foreign code used during the interview is only English. The second question to answer is the foreign words and phrases used to replace the Indonesian language. The study reveals the usage of eighty-three English words and phrases. The next question to answer is whether there are any appropriate Indonesian words and/or phrases to replace the foreign code used. The research shows that most of the English words and phrases used have their Indonesian substitutes. This research also intends to answer whether the grammar rules of the two codes match with each other. The study reveals that when the speakers metaphorically switch codes, they do not always follow the grammar rules of the native code. Finally, this research intends to answer the reasons underlying the speakers’ decision to metaphorically switch code. The result of the research shows five reasons behind the speakers’ decision to metaphorically switch code.